128k views
3 votes
Please help!!!  solve using principles of zero products. 6r(7r-6)(6r-1)=0

User Jloriente
by
8.0k points

2 Answers

1 vote

6r(7r-6)(6r-1)=0\\ 6r=0 \vee 7r-6=0 \vee 6r-1=0\\ r=0 \vee r=(6)/(7) \vee r=(1)/(6)
4 votes
This is beautiful, because they already gave it to you in factored form.

All you have to do is say to yourself "This equation is a true statement
when the left side is zero, and the left side is zero whenever ANY ONE
of the factors is zero.". Then jump on it and beat it up.

First factor:
6r = 0
r = 0

Second factor:
7r - 6 = 0
7r = 6
r = 6/7

Third factor:
6r - 1 = 0
6r = 1
r = 1/6
User Scottb
by
7.4k points